Association between serum sodium and in-hospital mortality among critically ill patients with spontaneous subarachnoid hemorrhage - Jin, Dongcai; Jin, Shaofeng; Liu, Bingyang; Ding, Yi; Zhou, Fen; Jin, Yuhong (Frontiers in Neurology, 2022)
Objective The aim of this study was to retrospectively explore the relationship between serum sodium and in-hospital mortality and related factors in critically ill patients with spontaneous subarachnoid hemorrhage (SAH). Methods Data were collected from the Medical Information Mart for Intensive Care IV database. Restricted cubic splines were used to explore the relationship between serum sodium and in-hospital mortality. Receiver operating characteristic analysis was used to calculate the optimal cutoff value of sodium fluctuation, and decision curve analysis was plotted to show the net benefit of different models containing serum sodium. Results A total of 295 patients with spontaneous SAH were included in the retrospective analysis. The level of sodium on ICU admission and minimum sodium in the ICU had a statistically significant non-linear relationship with in-hospital mortality (non-linear P-value < 0.05, total P-value < 0.001). Serum sodium on ICU admission, minimum serum sodium during ICU, and sodium fluctuation were independently associated with in-hospital mortality with odds ratios being 1.23 (95% confidence interval (CI): 1.04–1.45, P = 0.013), 1.35 (95% CI: 1.18-1.55, P < 0.001), and 1.07 (95% CI: 1.00–1.14, P = 0.047), respectively. The optimal cutoff point was 8.5 mmol/L to identify in-hospital death of patients with spontaneous SAH with sodium fluctuation, with an AUC of 0.659 (95% CI 0.573-0.744). Conclusion Among patients with spontaneous SAH, we found a J-shaped association between serum sodium on ICU admission and minimum sodium values during ICU with in-hospital mortality. Sodium fluctuation above 8.5 mmol/L was independently associated with in-hospital mortality. These results require being tested in prospective trials.